Diseño conceptual de la extracción de celulosa presente en la borra de café por medio de una digestión Kraft (2022)
The present work exposes an alternative for the use of coffee grounds (SCG), because Colombia is a coffee country and SCG is one of the main residues resulting from the processing of coffee beans, for which an overview is initially provided. of coffee production and the different residues generated. Subsequently, the bibliographic search is carried out to establish the amount of coffee processed in different factories in the country, together with the SCG generated by each one and the use they give it. In order to establish as a calculation base 20% of the SCG produced by the Buencafé plant located in the municipality of Chinchiná in the department of Caldas, since it is the one with the highest production.